(untitled) (Studia theodisca, 2022)
Goethe’s essay Einfache Nachahmung der Natur, Manier, Stil is steeped in an analogy: The life science of botany serves as an aesthetic foil, botany and art are set in parallel – to show how Goethe develops this, and what it implies, is the aim of this paper.